Study of Validity of PC-3 Derived Xenograft Tumor Model in Athymic Nude Mice for Targeting Therapy of Androgen Receptors in Preclinical Studies of Prostate Cancer - Samad Muhammadnejad; Ahad Muhammadnejad; Zohreh Mazaheri; Farrokh Tirgari; Mohammad-Ali Oghabian; Maryam Kazem haghighi; Saeid Amanpour (Basic & Clinical Cancer Research, 2016)
Background: Androgen receptors (AR) play an important role in proliferation of cancerous prostatic cells and prevention of apoptotic signaling. Current drugs cannot inhibit the activity of these receptors very well. Establishment of appropriate animal models is essential for discovery of new drugs of target therapy in hormone dependent prostate cancer. Materials and Methods: Standard prostatic cancer cell line (PC-3) was injected heterotopically into 9 nude mice. After tumor formation they were excised and sent for histopathologic and AR expression studies by immunohistochemistry. Results: Histological characteristics of prostate cancer were confirmed. Androgen receptors had been expressed in 65 Â± 25% of the xenograft tumor cells. Conclusions: This xenograft model is suitable for pharmacological and molecular studies of androgen dependent prostate cancer.